Semejanzas y diferencias por región en la educación: El caso de la educación matemática (ING) - Chaves Esquivel, Edwin (2003)
The present article reveals important regional differences regarding education in Costa Rica. After the analysis of multiple data, we discover the existence of many inequalities, like size, demographic density and age distribution (percentage of youths). On the other hand, we describe the most important aspects of teachers professional status, students achievement in national standardized tests, literacy, etc. Rural regions scattered over large areas of the country with smaller populations achieve a lower performance with fewer opportunities than other regions. To conclude, we urge the authorities and the whole educational system to move to correct these inequalities.